KINEMATIC ANALYSIS OF THE DEPLOYABLE TRUSS STRUCTURES FOR SPACE APPLICATIONS doi: 10.5028/jatm.2012.04044112 - Xu Yan; Guan Fu-ling; Zheng Yao; Zhao Mengliang (Journal of Aerospace Technology and Management, 2012)
Deployable structure technology has been used in aerospace and civil engineering structures very popularly. This paper reported on a recent development of numerical approaches for the kinematic analysis of the deployable truss structures. The dynamic equations of the constrained system and the computational procedures were summarized. The driving force vectors of the active cables considering the friction force were also formulated. Three types of macroelements used in deployable structures were described, including linear scissor-link element, multiangular scissor element, and rigid-plate element. The corresponding constraint equations and the Jacobian matrices of these macroelements were formulated. The accuracy and efficiency of the proposed approach are illustrated with numerical examples, including a double-ring deployable truss and a deployable solar array.